A virtual online environment for testing the effect of social and physical context on the effectiveness of health warning messages - Glance, D.; Berman, Y.; Pettigrew, S.; Jongenelis, M.; Chikritzhs, Tanya; Liang, W.; Pratt, I.; Slevin, T. (2017)
© 2017 IEEE. Testing the effectiveness of warning statements designed to encourage healthy lifestyle behaviours is largely done by showing the messages to study participants in the absence of 'real world' social and physical contexts. This approach does not factor in the impact of the medium of the message. A virtual, 360-degree environment (Messaging360) was developed that online participants can explore and be exposed to messages in a variety of different social and physical contexts: through advertising in a newspaper, labels on products and from a small child and a doctor avatar. The platform allows for large numbers of participants to be tested in a way that models real-life contexts for the messages and so may represent a more effective way of assessing their impact in delivering the health information.